Pregnancy outcomes in women with inflammatory bowel disease: a 10‐year nationwide population‐based cohort study. Issue 9 (7th April 2020) - Lee, Han H.; Bae, Jung Min; Lee, Bo‐In; Lee, Kang‐Moon; Wie, Jeong H.; Kim, Jin S.; Cho, Young‐Seok; Jung, Sung‐Ae; Kim, Sang W.; Choi, Hwang; Choi, Myung‐Gyu
Summary: Background: Data relating to the association between inflammatory bowel disease (IBD) and pregnancy outcomes are lacking in Korea. Aims: To determine the incidence rates of pregnancy outcomes in women with IBD. Methods: A nationwide population study was performed using the Korean National Health Insurance claims database. A total of 2058 women with IBD consisting of ulcerative colitis (UC, n = 1469) and Crohn's disease (CD, n = 589) were pregnant between 2007 and 2016. We compared their incidence of pregnancy outcomes with 20 580 age‐matched controls without IBD. We also stratified the patients into those with quiescent to mild and moderate to severe IBD and compared the outcomes between them. Results: The pregnancy rate of women with IBD was lower than that of women without (25.7% vs 32.3%, P  < 0.001). Caesarean section (46.5% vs 38.8%, odds ratio [OR] 1.43, 95% confidence interval [CI]: 1.17‐1.75), and intrauterine growth retardation (IUGR) (3.0% vs 1.0%, OR 2.89, 95% CI: 1.59‐5.26) were increased in CD patients than the controls. In regards to disease severity, there were no significant differences in pregnancy outcomes between patients with quiescent to mild IBD and the controls. However, the live birth rate of patients with moderate to severe IBD was lower than that of the controls (65.0% vs 69.9%, OR 0.79, 95%CI: 0.66‐0.94). In addition, moderate to severe IBD was significantly associated with spontaneous abortion (14.9% vs 11.9%, OR 1.33, 95% CI: 1.04‐1.68), caesarean section (46.4% vs 38.8%, OR 1.41, 95% CI: 1.14‐1.74) and IUGR (3.4% vs 1.0%, OR 3.20, 95% CI: 1.75‐5.84). Conclusions: With the exception of moderate to severe disease, the incidences of adverse pregnancy outcomes in women with IBD are similar to that of the general population.